Dual inorganic–organic flocculating systems for treatment of oil sands tailings - Mahmoudkhani, A; Tellakula, R; Stewart, K; Watson, P; Kolla, H (Paste 2013: 16th International Seminar on Paste and Thickened Tailings, 2013)
One of the major operational and environmental challenges facing Canada oil sands mining is the separation of water from the fines in tailing ponds in order to accelerate consolidation of tailings and to strengthen mine deposits so they can be reclaimed. Energy Resources Conservation Board (ERCB) Directive 074, released in February 2009 by the Alberta government, urges oil sands producers to accelerate the pace of developing tailings technologies for the consolidation and reclamation of tailings ponds. With no unique and acceptable solution yet in sight, research is now focusing on schemes which utilise more than one technology and combining them into a solution package which is both technically and economically viable. In this work, treatment of oil sands process tailings with combinations of inorganic and organic flocculants was investigated. Process fluid tailings were obtained from hot water extraction of low and high grade ores using a laboratory scale hydrotransport loop. Dual coagulants, coagulant-flocculant and dual flocculant systems were investigated. The effects of particle size distribution (PSD) on stratification after gravity settling and centrifuging with and without the addition of polymeric flocculants were examined, while mechanical properties were determined rheologically. Effects of charge density and molecular weight of organic polymers, in relation to charge and dosage of inorganic coagulants, were also studied. Results from the separation and dewatering of tailings indicate several advantages of dual inorganic–organic flocculation over traditional single coagulation or flocculation methods. A synergistic effect due to intermolecular interactions between inorganic–organic polymers was found to have a marked effect, yielding enhanced agglomeration and dewatering of oil sands tailings. This approach was found to be relatively less sensitive to water chemistry and to the method for water-solid separation. Through systematic studies using in-line PSD analysis and quartz crystal microbalance with dissipation for adsorption analysis, it was found that the use of a blend of polymers with various charges and molecular weights ensures that all minerals present in tailings are effectively flocculated and separated from fine fluid mix.